Performance Appraisal and Promotion Practices of Public Commercial Banks in Bangladesh- A Case Study on ACR Method - Nishath Anjum; Md. Mashfiqur Rahman (SEISENSE Journal of Management, 2021)
Purpose- Performance appraisal is crucial for enhancing the productivity of employees working in any sector. This paper investigates the prevailing performance appraisal system and promotion policy of selected public commercial banks (Sonali Bank Ltd, Rupali Bank Ltd, and Agrani Bank Ltd) in Bangladesh.